ARE HUMAN CELL LINES HUMAN? - Thomas K. Nelson (European Scientific Journal, ESJ, 2015)
Among the most novel and startling objects in the biological world discovered and developed by modern science is the phenomenon of human cell lines: living cells separated from living bodies and living and reproducing in laboratories over extended periods of time. This scientific status and utility of such cells is first reviewed, distinguishing cell cultures from cell strains and cell lines. Next, the ontological status of cell lines is reviewed in the tradition of philosophia perennis, and it is asserted that cell lines are neither formally human as extensions of human life or human parts, nor materially human in configuration; rather, they are new organisms animated by a vegetative soul, despite the biological continuity between a human being and a human cell line. Such cells can be conceptualized as having undergone substantial change from human part to individual vegetative life forms, or as virtually present in the human being with the potency like elements in a mixture to emerge from the composite and exist under highly specific and artificial conditions.